Correlation between Hematologic Parameters and Asymptomatic Bacteriuria in the Full-Term Pregnant Patients in Dr. Kariadi Hospital, Semarang, Indonesia - Muhamad Sukri (Diponegoro International Medical Journal, 2022)
Objective: We investigated the role of hematologic parameter such as hemoglobin, white blood  cells, platelet, hemoglobin platelet ratio (HPR), hemoglobin white blood cells ratio (HWR) in  full-term pregnant patients and correlate the result with their urine culture following delivery.  Methods: Between 2019-2020, a total number of 95 pregnant patients were retrospectively  evaluated at the maternal ward.Results: The average age of the subjects was 29.15 (SD ± 5.95), median of parity of 2 (range 1- 4) and mean of gestational age was 37.5 (SD ± 1.67). There is no difference between groups on  the surgery types and comorbidities condition. Among the patients, 14 urine cultures produced  growth of 105 CFU/ml bacteria. Pearson’s correlation test showed that leukocyte inversely  correlated with bacteriuria, meanwhile hemoglobin white blood cell ratio (HWR) is positively  correlated with urinary culture result. In the diagnostic performance, HWR had AUC of 0.765  with sensitivity and specificity of 78.6% and 64.2% respectively at the cut off of 11.92.Conclusions: Prediction of asymptomatic bacteriuria in pregnant patient by simple calculation of  HWR might be helpful in significantly reducing workload and costs of urine culture. It is a great  advantage that the parameters we use in our work are easily accessible and can be performed in  emergency conditions.